PEMANFAATAN TEKNOLOGI DIGITAL OLEH GURU PAI DALAM MENINGKATKAN MUTU PEMBELAJARAN PADA ERA SOCIETY 5.0 DI MADRASAH TSANAWIYAH - Intan Nuraini; Imaniar Mahmuda (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT The development of digital technology in the society 5.0 era requires teachers to be able to utilize technology in creating learning processes that are more effective, interactive, and aligned with students’ needs. This study aims to describe the use of digital technology by Islamic Education (PAI) teachers to improve the quality of learning in the Society 5.0 era, as well as to identify the supporting and inhibiting factors at MTs SA Miftahul Ulum Curahkalong Bangsalsari, Jember. This study employs a descriptive qualitative approach using the case study method. Data were collected through observation, in-depth interviews, and documentation. The results indicate that PAI teachers have utilized digital technology in the planning and teaching processes, such as the use of LCD projectors, laptops, and Wi-Fi, as well as Microsoft Word and Microsoft Excel. This utilization has successfully increased student engagement, understanding of the material, and learning outcomes; furthermore, Islamic values can be integrated into digital technology as part of the learning process. However, this study is not without challenges, such as infrastructure limitations and human resource constraints. The utilization of digital technology by Islamic Education (PAI) teachers has proven effective in improving the quality of learning, students’ learning interest, and classroom participation, although there are still obstacles such as limited internet access and supporting facilities. ABSTRAK Perkembangan teknologi digital di era society 5.0 menuntut guru untuk mampu memanfaatkan teknologi dalam menciptakan pembelajaran yang lebih efektif, interaktif, dan sesuai dengan kebutuhan peserta didik. Penelitian ini bertujuan untuk mendeskripsikan pemanfaatan teknologi digital oleh guru PAI dalam meningkatkan mutu pembelajaran di era society 5.0, serta mengindentifikasi faktor pendukung dan penghambatnya di MTs SA Miftahul Ulum Curahkalong Bangsalsari Jember. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Data diperoleh melalui observasi dan wawancara mendalam, serta dokumentasi. Hasil penelitian menunjukkan bahwa guru PAI telah memanfaatkan teknologi digital dalam proses perencanaan dan pembelajaran, seperti penggunaan LCD proyektor, laptop dan Wi-Fi, juga Microsoft Word dan Microsoft Excel. Pemanfaatan tersebut telah mampu  meningkatkan keaktifan siswa, pemahaman materi, serta hasil belajar, selain itu nilai Islami dapat digabungkan dalam teknologi digital sebagai bagian dari proses pembelajaran. Namun, penelitian ini tak lepas dari tantangan, seperti keterbatasan infrastruktur dan keterbatasan sumber daya manusia. Pemanfaatan teknologi digital oleh guru PAI terbukti efektif dalam meningkatkan mutu pembelajaran, minat belajar, dan keaktifan siswa, meskipun masih terdapat hambatan berupa keterbatasan jaringan internet dan fasilitas pendukung.